Prototype of Drainage Water Level Monitoring System Using Internet of Things (IoT) Based Web - Sihombing, Jaya; Jaenul, Ariep; Wilyanti, Sinka; Putri, Nadya (Universitas PGRI Kanjuruhan Malang, 2022)
Information on water levels needs to be conveyed quickly. So, when the rainfall is high, the supervisory team that monitor the drainage water level needs to be alert move quickly to prevent losses. In addressing these problems, the author will provide a solution in Monitoring of the water level system in the drainage water reservoir so that the operator and maintenance team can find out if there is an over discharge in the drainage water reservoir when the rainfall is very high. By utilizing ultrasonic sensors to detect changes in drainage water level. The ultrasonic sensor used has better reliability than other proximity sensors. In addition, the use of the ultrasonic sensor capability on the prototype is only on the Centimeter scale, and with the help of a buzzer as a reminder indicator (alarm) to find out the water level approaching the sensor. Float switch is also used to determine the water level, namely low, medium and high.